2018
DOI: 10.1016/j.neulet.2017.11.039
|View full text |Cite
|
Sign up to set email alerts
|

17β-estradiol locally increases phasic dopamine release in the dorsal striatum

Abstract: Studies using in vivo microdialysis have shown that 17β-estradiol (E2) increases dopamine (DA) transmission in the dorsal striatum. Both systemic administration of E2 and local infusion into the dorsal striatum rapidly enhance amphetamine-induced DA release. However, it is not known to what degree these effects reflect tonic and/or phasic DA release. It was hypothesized that E2 acts directly within the DS to rapidly increase phasic DA transmission. In urethane-anesthetized (1.5mL/kg) female rats, we used fast-… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
11
0

Year Published

2018
2018
2022
2022

Publication Types

Select...
8

Relationship

1
7

Authors

Journals

citations
Cited by 16 publications
(11 citation statements)
references
References 24 publications
0
11
0
Order By: Relevance
“…So far, studies have well established that estrogens modulate DA neural activity in the dorsal striatum. [42][43][44] Even in humans, direct infusion of estrogen into the dorsal striatum increased DA release, 45,46 and this enhancing effect of E2 is mediated by E2 receptors and mGlu5 receptors. 46 Animal and human studies suggest increased striatal D1 and D2 receptor density in periovulatory versus follicular phases in menstruating women.…”
Section: Discussionmentioning
confidence: 99%
“…So far, studies have well established that estrogens modulate DA neural activity in the dorsal striatum. [42][43][44] Even in humans, direct infusion of estrogen into the dorsal striatum increased DA release, 45,46 and this enhancing effect of E2 is mediated by E2 receptors and mGlu5 receptors. 46 Animal and human studies suggest increased striatal D1 and D2 receptor density in periovulatory versus follicular phases in menstruating women.…”
Section: Discussionmentioning
confidence: 99%
“…Preclinical evidence suggests that endogenous estradiol levels can increase dopamine release in the reward system, specifically in the striatum [62, 63]. Behavioral studies in humans partly support this finding as a positive correlation between endogenous estradiol levels and enhanced reward sensitivity in women, but paradoxically no increase in motivation for higher rewards from the early to the late follicular phase (i.e., with rising endogenous estradiol levels) have been reported [64].…”
Section: Influence Of Hcs On Psychological and Neurophysiological Mecmentioning
confidence: 98%
“…However, baseline ventral tegmental area activity and phasic dopamine release is similar between the sexes in the nucleus accumbens [118]. Electrically stimulated phasic dopamine release is higher in estrous females (when estradiol levels are high) compared to males or females in low-estradiol stages [100,101,103,118]. [8] Estrous-associated increases in ventral tegmental area firing and dopamine release increase phosphorylation of DAT at threonine 53 (Thr53), which increases the affinity of cocaine for DAT.…”
Section: Key Playersmentioning
confidence: 99%
“…In females, extracellular dopamine varies with the estrous cycle [97] and is dependent on the actions of estradiol in the striatum. Estradiol acts directly in dorsal striatum to enhance stimulated dopamine release in OVX female, but not CAST male rats [97,[99][100][101][102]. In possible contrast to the above results using microdialysis, which provides a slower time course of extracellular dopamine release, in vivo and in vitro experiments in rats using fast scan cyclic voltammetry, which measures phasic dopamine release in real time, has shown that electrical stimulation of the ventral tegmental area and cocaine-induced dopamine release and uptake rates are greater in the female, compared to the male, striatum-regardless of estrous cycle stage, which may underlie the lower basal dopamine concentrations found with microdialysis [103].…”
Section: Key Playersmentioning
confidence: 99%